From an online survey: the dilemma of religious education model in Indonesia affected to inter-group contact - Sulaiman Sulaiman (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Legally, Indonesia adheres to a preference for religious education with a mono-religious model. Ideally, every adherent of an institutional religion registered in Indonesia has the right to receive religious education according to their respective religions. This is also in accordance with international human rights law. Through this study, it was found that not all religious adherents received religious education according to their religion. Although there are respondents who have experience following religious education in accordance with their religion, view other groups negatively and feel disturbed by the activities of other religious groups, in general this study shows that those who belong to diverse religious groups do not experience difficulties in inter-group contact.